Bacterial causes and antibiotics susceptibility profile of surgical site infection following cesarean section - Gordana Bogdanović; Anis Cerovac; Elmedina Cerovac; Dubravko Habek; Fatima Numanović; Amela Bećirović; Bedrana Muračević-Begović; Alma Jahić Čampara; Želimir Marinović (IMR Press, 2022)
Backround: Surgical site infection (SSI) is defined as an infection occurring within 30 days after a surgical operation and affecting either incision or deep tissues at the operation site. The aim of this study was to examine the incidence, identify bacterial agents and determine their antibiotics sensitivity of SSI following cesarean section (CS). Methods: This retrospective cohort study included women who undervent Misgav-Ladach method CS after which a SSI developed during the period from 01 January 2019 to 31 December 2019 at the Clinic for Gynecology and Obstetrics, University Clinical Center Tuzla. Results: During the observed period we recorded 3345 deliveries, out of which 946 (28.3%) were by cesarean section, and out of which 50 (5.28%) was with SSI. The most commonly isolated bacteria from SSI were: Escherichia coli; Enterococcus faecalis; Staphylococcus aureus; Klebsiella pneumoniae. Fluoroquinolnes had the highest antibacterial activity against gram-positive pathogenes isolated. Staphylococcus aureus isolates is highly resistant to penicilline (100%). Conclusions: The prevalence of SSI following cesarean section was high and Enterococccus faecalis and Escherichia coli was the commonest pathogens isolated.